Teacher's Efforts in Practicing Beginning Writing Skills for Elementary Level Students Using the Drill Method - Setiaji Nur Zaman; Pratiwi Rahmah Hakim (JENIUS (Journal of Education Policy and Elementary Education Issues), 2022)
The implementation of the drill method is a form of effort made by the teacher to train students' skills in learning initial writing skills. The low writing skills of first-grade students are a challenge for a teacher, so a learning innovation using the drill method is needed to train students in properly and correctly composing words or sentences. The purpose of this study was to determine the implementation of the drill method in learning this beginning writing skill for class 1C students at MI Al Islam, conducted from February to May 2021. This research used a qualitative descriptive type approach. The subjects of this study were class 1C teachers, and the informants of this study were class 1C students and the head of MI. Data was obtained through observation, interviews, and documentation. The data validation technique uses source, technical, and theory triangulation. Meanwhile, analyse the data in this study using data collection, reduction, presentation, and conclusion. Implementing the drill method through repeated exercises can train students' initial writing skills, because it can stimulate their memory abilities